IgG4-related disease presenting as a pancreatic mass: A case report - Lutf, Abdo; Joudeh, Anwar Ibrahi; Mehdi, Salah M (Eastern Journal of Medical Sciences, 2024)
Immunoglobulin G4-related disease (IgG4-RD) is an increasingly recognized fibroinflammatory condition with characteristic clinical, serological, and histopathological features. It might involve any organ in the body with a special predilection for lymph nodes, salivary glands, the pancreas, and the retroperitoneum. Due to the non-specific features of the disease and the capability of mimicking many other medical conditions, the diagnosis of IgG4-RD could be delayed. Herin, we describe a case of a middle-aged man who presented with obstructive jaundice due to a pancreatic mass. Further evaluation revealed multiple cervical and inguinal lymphadenopathy, bilateral wedge-shaped lesions in the kidneys and substantial thickening of the aortic wall that was suggestive of aortitis/periaortitis. A histopathological examination of an inguinal lymph node showed increased infiltration of nodal immunoglobulin G4 (IgG4) plasma cells (>30/high-power field) with a high serum IgG4 immunoglobulin level. Based on that, the patient was diagnosed with IgG4-RD, and he was successfully treated with pulse steroid therapy with complete resolution of his symptoms and the radiological and laboratory findings. IgG4-RD is a protean condition with a large spectrum of clinical manifestations that could mimic many other serious medical conditions. Early recognition and management of immunosuppression are vital for complete recovery.